Examining the Informational Role of Analysts’ Forecasts and its Impact on the Relation between Earnings Surprises and Investors’ Responses - LEE, Joonho (Institutional Knowledge at Singapore Management University, 2013)
Prior research documents the existence of two distinct post-earnings-announcement-drifts. Interestingly, investors seem to underreact more toward analyst-based earnings surprises than toward seasonal random walk earnings surprises. In this paper, we measure the extent of investors’ delayed reaction relative to the total market response to the earnings surprises. Using this measure, we find that investors react proportionately faster and more thoroughly to analyst-based earnings surprises than to random walk earnings surprises, suggesting that analyst-based earnings surprises are relatively less related with a delayed investor reaction compared with random walk earnings surprises. We also find that as the informativeness of analyst earnings forecasts increases, investors’ response to earnings surprises increases more in instant form than in delayed form. In contrast, as the informativeness of random walk earnings expectations increases, investors’ delayed response increases more than their instant response. Finally, we find that investors’ faster and more thorough response to analyst-based earnings surprises increases in the quality of the firms’ information environment. Our results complement existing research findings by utilizing a relative PEAD measure and provide a greater understanding toward the interpretation of both drifts.